Integrative review of studies in the field of psychology on the social representations of body image: what academic productions say (Research, Society and Development, 2021)
The present study addresses the importance of the concepts of social representation that encompasses the body and the perception of the body's image in the context of contemporaneity. The main objective is to analyze the perception of body image and its influence on biopsychosocial health, according to the subjectivities of each subject and the media influences exerted by each society in a generational way. This study corresponds to a bibliographic study, carried out through the formal platforms of the Catalog of Theses and Dissertations (CAPES), Google Scholar and Digital Library of Theses and Dissertations (BDTD), using a total of six articles for research, for the result and discussion . Based on the assumption, social representations are part of the life context of each and every individual who is inserted in a certain society, in which the relationship that the media exercises over bodies produces subjective content has the function of guiding the body in order to determine patterns esthetics in which the subjects guide their attitudes and behaviors towards themselves and the other. The data reveal that the perception of body image is linked to representational content that is part of a social construction, in which the subject is willing to follow standards and rules according to the environment in which he is inserted. There is, then, a fine distinction between beauty and health that disregards the negative effects of the body, which, in turn, can lead to the growth of subjects with disorders related to body image.